2016
DOI: 10.1186/s12944-016-0374-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of low high-density lipoprotein-cholesterol level on 2-year clinical outcomes after acute myocardial infarction in patients with diabetes mellitus

Abstract: BackgroundIt is still unclear whether low high-density lipoprotein cholesterol (HDL-C) affects cardiovascular outcomes after acute myocardial infarction (AMI), especially in patients with diabetes mellitus.MethodsA total of 984 AMI patients with diabetes mellitus from the DIabetic Acute Myocardial InfarctiON Disease (DIAMOND) Korean multicenter registry were divided into two groups based on HDL-C level on admission: normal HDL-C group (HDL-C ≥ 40 mg/dL, n = 519) and low HDL-C group (HDL-C < 40 mg/dL, n = 465).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Dyslipidemia is characterized by elevated triglyceride (TG) and reduced dense high-density lipoprotein cholesterol particles levels, and lower high-density lipoprotein cholesterol (HDL-C) levels in diabetic patients (7,8). Elevated TG and lower HDL-C are associated with poor prognosis in diabetic patients (9)(10)(11)(12), but the use TG or HDL-C alone does not reflect the risk of atherosclerosis and cardiovascular disease (CVD) (13). The TG/HDL-C ratio may reflect the actual lipid profiles, and is considered an important marker of plasma atherosclerosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia is characterized by elevated triglyceride (TG) and reduced dense high-density lipoprotein cholesterol particles levels, and lower high-density lipoprotein cholesterol (HDL-C) levels in diabetic patients (7,8). Elevated TG and lower HDL-C are associated with poor prognosis in diabetic patients (9)(10)(11)(12), but the use TG or HDL-C alone does not reflect the risk of atherosclerosis and cardiovascular disease (CVD) (13). The TG/HDL-C ratio may reflect the actual lipid profiles, and is considered an important marker of plasma atherosclerosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…In an observational study conducted in Korea, cardiovascular events were shown to have a high prevalence in DM populations with a low HDL-C concentration. 33 In a retrospective cohort study conducted by Squillace et al, 34 a high TG/HDL ratio was found to predict the risk of new-onset DM independent of other traditional risk factors. Taken together, these findings suggest that levels of HDL-C and TGs may represent important early markers of DN and DM.…”
Section: Discussionmentioning
confidence: 96%
“…Dyslipidemia is characterized by higher triglyceride (TG) levels, lower high-density lipoprotein cholesterol (HDL-C) levels and increased small dense high-density lipoprotein cholesterol(sd-LDL) particles in patients with T2DM [7,8]. It has been demonstrated that elevated serum TG and reduced HDL-C levels contribute to poor prognosis in patients with T2DM [9][10][11][12]. However, TG and HDL-C levels alone do not re ect the actual status of plasma atherogenicity and cardiovascular disease (CVD) risk [13].…”
Section: Introductionmentioning
confidence: 99%